The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-12076-1
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway asymmetry in skeletal Class III malocclusions with mandibular deviation

Abstract: The purpose of this study was to investigate the relationship between bilateral differences of upper airway and mandibular morphologic patterns in subjects with skeletal Class III mandibular deviation. 47 skeletal Class III (ANB < 0°) adult patients with and without mandibular deviation were divided into 2 groups. Bilateral differences of minimum cross-sectional area, mean cross-sectional area, volume of subdivisions (nasopharynx, palatopharynx, glossopharynx, hypopharynx) were assessed paired t test. Stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…Differences in airway parameters were observed between the deviated and non-deviated sides of airway space, especially in C2C and C3C which were significantly larger on the deviated side than on the non-deviated side (Table S1). These findings are consistent with the results of Zheng et al 21 who reported that Class III mandibular-deviated group presented with significant asymmetry, characterized by larger mean cross-sectional area and volume on the deviated side than on the J o u r n a l P r e -p r o o f non-deviated side in the glossopharyngeal segment and hypopharyngeal portion. These results suggest that mandibular asymmetry may contribute to pharyngeal airway collapsibility and pharyngeal compliance, which increases morbidity of obstructive sleep apnea (OSA).…”
Section: Discussionsupporting
confidence: 92%
“…Differences in airway parameters were observed between the deviated and non-deviated sides of airway space, especially in C2C and C3C which were significantly larger on the deviated side than on the non-deviated side (Table S1). These findings are consistent with the results of Zheng et al 21 who reported that Class III mandibular-deviated group presented with significant asymmetry, characterized by larger mean cross-sectional area and volume on the deviated side than on the J o u r n a l P r e -p r o o f non-deviated side in the glossopharyngeal segment and hypopharyngeal portion. These results suggest that mandibular asymmetry may contribute to pharyngeal airway collapsibility and pharyngeal compliance, which increases morbidity of obstructive sleep apnea (OSA).…”
Section: Discussionsupporting
confidence: 92%
“…The neurological control of upper airway muscles plays a role in OSA too, as reduced muscle tone during sleep can lead to airway collapse [ 84 , 85 , 86 , 87 ]. Personalized treatment targeting this pathophysiological mechanism could include therapies to enhance the tone and function of these muscles, possibly through neuromuscular electrical stimulation or targeted exercises [ 88 ].…”
Section: Obstructive Sleep Apnea As a Case Studymentioning
confidence: 99%
“…Lung function and respiratory control mechanisms also contribute to OSA, particularly in individuals with underlying respiratory diseases [ 84 , 85 , 86 , 87 ]. Management might involve using positive airway pressure therapies, such as CPAP, to keep the airway open, or addressing underlying respiratory conditions.…”
Section: Obstructive Sleep Apnea As a Case Studymentioning
confidence: 99%